Interest towards entrepreneurship among bachelor students in faculty of business management at Universiti Teknology MARA (UiTM) Jengka Pahang / Nur Haslynda Ahmad Saleh - Ahmad Saleh, Nur Haslynda (2014)
The study entitled "Interest Towards Entrepreneurship Among Bachelor Students In Faculty Of Business Management In Universiti Teknologi Mara (UiTM) Jengka, Pahang". The aim of this study is to investigate the level of interest towards entrepreneurship among Faculty of Business Management in this university. This paper attempts to examine whether entrepreneurship background, business involvement and entrepreneurship program will affect the entrepreneurial interest of the students. This research more focused to students Bachelor in Business Management and 161 respondents was selected to fulfill and completed the questionnaire. At the end of this paper have several recommendation for the future research purpose.